Biochar boosts dark fermentative H2 production from sugarcane bagasse by selective enrichment/colonization of functional bacteria and enhancing extracellular electron transfer. (1st September 2021) - Bu, Jie; Wei, Hao-Lin; Wang, Yu-Tao; Cheng, Jing-Rong; Zhu, Ming-Jun
Highlights: BC pyrolyzed at 600°C significantly boosted H2 production from PSCB. BC implemented selective enrichment and colonization of functional bacteria. BC stimulated synergistic effect and activated EET between functional bacteria. New insight in understanding improved AD performance by BC was proposed. Abstract: The influence of biochar (BC) on anerobic digestion (AD) of organic wastes have been widely studied. However, the effect of BC on rate-limiting step during AD of lignocellulosic waste, i.e. the hydrolysis and acidogenesis step, is rarely studied and the underlying mechanisms have not been investigated. In this study, the benefits of BC with respect to dark fermentative hydrogen production were explored in a fermentation system by a heat-shocked consortium from sewage sludge (SS) with pretreated sugarcane bagasse (PSCB) as carbon source. The results showed that biochar boosted biohydrogen production by 317.1% through stimulating bacterial growth, improving critical enzymatic activities, manipulating the ratio of NADH/NAD + and enhancing electron transfer efficiency of fermentation system. Furthermore, cellulolytic Lachnospiraceae was efficiently enriched and electroactive bacteria were selectively colonized and the ecological niche was formed on the surface of biochar. Synergistic effect between functional bacteria and extracellular electron transfer (EET) in electroactive bacteria were assumed to be established and maintained by biochar amendment. This study shed light on the underlying mechanisms of improved performance of biohydrogen production from lignocellulosic waste during mesophilic dark fermentation by BC supplementation. Graphical abstract: Image, graphical abstract